Quantifying the Effect of Present, Past and Oncoming Alignment on the Operating Speeds of a Two-Lane Rural Road - Praticò, Filippo Giammaria; Giunta, Marinella (The Baltic Journal of Road and Bridge Engineering, 2012)
In the last decades several studies were conducted in order to develop operating speed prediction models for two-lane rural roads. Many factors were found to affect the operating speed, such as radius of horizontal curve or curvature changes rate, grade, length of horizontal curve, deflection angle, sight distance, superelevation rate, side friction factor, and pavement conditions. Though this, many issues arise when there is an appreciable and continuous variance of geometric features along the road and, for example, short and long tangents coexist in the same road. In such conditions, assessing homogeneous sections, calibrating robust algorithms aimed at V85 prediction is a severe task and safety goals are not easily achieved. In the light of the abovementioned facts, objective and scopes of this work were confined into the quantifications of the effect of past, present, and future geometric elements on operating speeds. In particular, attention was focused on the consistency of the assumption of an environmental speed as a reference value for both short (dependent) and long (independent) tangents. Authors proposed a new operating speed model in which the geometric features of the previous and oncoming alignment were explicitly considered. The proposed speed prediction algorithm was validated on the basis of a wide experimental survey carried out in a rural road of the Province of Reggio Calabria – southern Italy. Problem modelling, experimental plan and results discussion are reported. Results proved the validity of the proposed model even if further experiments are needed to make the model able to predict the operating speed in different type of roads.